PENGARUH MODEL PEMBELAJARAN DISCOVERY LEARNING TERHADAP HASIL BELAJAR DAN KEAKTIFAN SISWA PADA MATERI PERTUMBUHAN DAN PERKEMBANGAN TUMBUHAN KELAS XII SMA - Good Govermance Manihuruk; Mastiur Verawaty Silalahi; Srinatalia Silaen (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Nahdlatul Wathan Mataram, 2022)
This study aims to determine the effect of the Discovery Learning model in class XII SMA Swasta Abdi Sejati Trade. The researcher also wanted to prove whether student activity and learning outcomes had significant differences before and after treatment. This research was conducted at Abdi Sejati Trade Private High School for the Academic Year of 2022/2023. From the results of the study, the average value of the experimental class using the Discovery Learning model was 83.17 with a value of 7.130, and the average value of control was 76.33 with a value of 8.087. The N-gain for the experimental class using the Discovery Learning model is g = 0.66 which is the medium category, while the N-gain for the control class is g = 0.51 which is the medium category. Therefore, the increase in learning outcomes of the experimental class was higher than that of the control class. Based on the hypothesis test obtained tcount as much as 0.444. Then it is known that the value of tcount > table. Based on the significance value, the resulting value is 0.594 which shows the significance value > 0.05. So it can be said that this research Ha is accepted and Ho is rejected or there is an effect of the use of the Discovery Learning model on learning outcomes and student activity on plant growth and development materials.